Overview of big data in smart grid - Shobole, Abdulfetah; Ali, Mbarak Hamid; Wadi, Mohammed; Tur, Mehmet Rıda; Wadi, Mohammed; Shobole, Abdulfetah Abdela (Institute of Electrical and Electronics Engineers Inc., 2019)
The integration of Electrical power with advanced information and communication technologies has led to an intelligent electricity grid known as the Smart Grid. The Smart Grid has also led to the improvement of the entire energy flow system through a bidirectional flow of power and information between utility and consumer, hence making the system safe, efficient and reliable. Big data in smart grid are very significant and visible due to the accumulation of the increasing volumes of data. This data is accessed by the electrical utilities as well as customers from smart meters, power management units (PMUs), supervisory control and data acquisition (SCADA) systems, frequency disturbance recorders (FDRs), outage management systems, wide-area monitoring system (WAMS), field devices, customer billing software, customers' data, sensors, computers and communication networks all integrated into the power network. Therefore, big data has a great significance in the establishment of a better Smart Grid. This paper introduces smart grid and its concepts, the role of big data in smart grid; challenges faced by big data in smart grid and the prospect of the big data in smart grids. © 2019 IEEE.
Fujitsu;Honda;JR-East Group;Nissan Motor Corporation;TMEic
8th International Conference on Renewable Energy Research and Applications, ICRERA 2019 -- 3 November 2019 through 6 November 2019 -- -- 157837
Keywords: Big Data; Big Data Challenges; Data Management; Grid Modernization; Smart Grid